Pengaruh Return on Asset (ROA) dan Earning Per Share (EPS) Terhadap Harga Saham (Studi pada Perusahan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia) - Maja Wally; Jaelani Lamasidonda; Jusuf Sahupala (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this study is to empirically examine the effect of Return on Assets (ROA) and Earnings Per Share (EPS) on stock prices. The analytical tool used in this study was multiple linear regression. The total population of 29 companies or all banking sector companies listed on the IDX in 2016, sampling techniques using the purposive sampling method, which was sampled in this study were as many as 12 banking companies. The results showed that the variable ROA (X1) had a significant effect on Stock Price, while EPS (X2) did not have a significant effect on Stock Price